Who Treats Adolescents and Young Adults with Cancer? A Report from the AYA HOPE Study - Parsons, Helen M. (J Adolesc Young Adult Oncol, 2015)
Purpose: Physicians play a critical role in delivering effective treatment and enabling successful transition to survivorship among adolescent and young adult (AYA) cancer patients. However, with no AYA cancer medical specialty, information on where and by whom AYAs with cancer are treated is limited. Methods: Using the National Cancer Institute's population-based AYA HOPE Study, 464 AYAs aged 15–39 at diagnosis treated by 903 physicians were identified. Differences in physician and hospital characteristics were examined by age at diagnosis and cancer type (germ cell cancer, non-Hodgkin lymphoma, Hodgkin lymphoma, acute lymphocytic leukemia [ALL], and sarcoma) using chi-square tests. Results: Treating physicians were predominately 51–64 years old, male, United States–trained in non-pediatric specialties, and in group practices within large metropolitan areas. Older patients were less often treated by pediatric physicians (p < 0.01) and more likely to be treated by United States–trained physicians without research/teaching responsibilities and in hospitals without residency programs (p < 0.05). The majority of the few pediatricians (n = 44) treated ALL patients. Physicians with research/teaching responsibilities and those based in medical schools were more likely to treat patients with ALL and sarcoma compared with other cancer types (p < 0.01). Of HL patients, 73% were treated at a cancer center compared with 56% of patients with germ cell cancer (p < 0.01), while ALL (85%) and sarcoma (87%) patients were more likely to be treated in hospitals with residency programs (p < 0.01). Conclusions: Most AYAs with cancer were treated by non-pediatric physicians in community settings, although physician characteristics varied significantly by patient cancer type and age at diagnosis.